Hybrid nerve sheath tumor of the spinal canal and neurofibromatosis-2, where the twain shall meet—a case report and review of literature - Deepak Nayak Manel; Shivam Thaker; Geetha Vasudevan; Girish Menon (Journal of Medical Case Reports, 2025)
Abstract Background A hybrid nerve sheath tumor is a biphasic, benign neoplasm of peripheral nerve sheaths, consisting of combinations of neurofibroma, schwannoma, or perineurioma. These tumors were recognized only recently, in 2013; they commonly occur sporadically but rarely with syndromic associations, such as neurofibromatosis syndrome, Carney complex, and schwannomatosis. With an occurrence of 1 in every 33,000 individuals, neurofibromatosis type 2 is a rare autosomal dominant condition characterized by bilateral vestibular schwannomas. Herein we report a serendipitous occurrence of a hybrid nerve sheath tumor with neurofibromatosis type 2 syndrome, with an emphasis on its diagnostic mimics. Case report A 35-year-old Indian male patient presented to the clinic with balance dysfunction, left-sided hearing loss, and spastic weakness in all four limbs during the past 6 months. Neurological examination revealed increased motor tone in all four limbs, bilateral 4/5 limb strength, a right grip strength of 80%, and a left grip strength of 90%. Romberg’s sign, Babinski sign (extensor), and Hoffman’s sign were positive. No cerebellar signs were elicited. A cranial nerve examination revealed bilateral hearing impairment, with hearing of the left being greater than that of the right. Magnetic resonance imaging revealed, an ependymoma at C1–2, a hyperintensive T2 lesion (likely a meningioma), a neurofibroma at C2, and bilateral vestibular schwannomas at the cerebellopontine angle. The patient underwent tumor excision surgery under somatosensory evoked potential/motor evoked potential monitoring. The tumor at the C2 level showed a nodular arrangement with typical schwannian nodules (SOX-10 strongly positive and epithelial membrane antigen negative); these nodules were encased by a hypocellular neurofibroma component (CD34+), forming a lattice around the former. No necrosis or increased proliferation index was noted. Conclusion Neurofibromatosis type 2 syndrome is a rare condition, associated with mutations in both alleles of the NF2 (Merlin) gene, and is associated with meningiomas and ependymomas, as seen in this patient. Its occurrence alongside a spinal hybrid nerve sheath tumor is rare and can often lead to an erroneous diagnosis of other nerve sheath tumors or, rarely, a malignant nerve sheath tumor. This case highlights this rare confluence and its mimickers.